THE CONNECTION MATHEMATICAL SELF-EFFICACY AND MATHEMATICAL REASONING IN ELEMENTARY SCHOOL STUDENTS - Regha Regita TR; wahyudin (Universitas Majalengka, 2024)
This research aims to examine the connection between mathematical self-efficacy and mathematical reasoning in elementary school students. The research used a quantitative method with a pretest-posttest experimental design in one experimental group, consisting of 27 fourth-grade elementary school students. In addition, the designed intervention aims to increase students’ mathematical self-efficacy through training and activities for 2 weeks. The results show a significant increase in mathematical self-efficacy, with the average score increasing from 65.4 on the pretest to 78.2 on the posttest (t value = 6.87, p < 0.001). Students’ mathematical reasoning also demonstrate a significant increase, from an average score of 62.8 on the pretest to 74.5 on the posttest (t value = 5.93, p < 0.001). furthermore, the correlation analysis indicates a significant positive connection between changes in mathematical self-efficacy and mathematical reasoning, with a correlation value (r) of 0.68 and p-value <0.01. Based on the research results, it can be concluded that the increase in mathematical self-efficacy is closely related to the improvement in students’ mathematical reasoning abilities. Moreover, this research provides valuable insight for educators in designing more effective and holistic learning strategies, focusing on improving students’ psychological aspects in addition to cognitive aspects.